2014
DOI: 10.1088/1748-6041/9/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

An integrated study of natural hydroxyapatite-induced osteogenic differentiation of mesenchymal stem cells using transcriptomics, proteomics and microRNA analyses

Abstract: This work combined transcriptomics, proteomics, and microRNA (miRNA) analyses to elucidate the mechanism of natural hydroxyapatite (NHA)-induced osteogenic differentiation of mesenchymal stem cells (MSCs). First, NHA powder was obtained from pig bones and fabricated into disc-shaped samples. Subsequently, the proliferation and osteogenic differentiation of MSCs cultured on NHA were investigated. Then, proteomics was employed to detect the protein expression profiles of MSCs cultured on NHA, and the effect of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
(97 reference statements)
0
15
0
Order By: Relevance
“…The osteomimetic hydroxyapatite and the cellular response to a-particles Hydroxyapatite is a calcium phosphate similar to the human bone in morphology and composition insofar as it has a hexagonal structure and a similar stoichiometric calcium-to-phosphate ratio (37). Hydroxyapatite has previously been shown to induce osteogenic differentiation from cellular precursors (38) and alter the transcriptome and proteome of cocultured cells (39). Because 223 Ra exerts its effect by incorporation into the bone, we sought to assess the impact of hydroxyapatite on cellular sensitivity to a-particles using a coincubation method (Fig.…”
Section: A-particle Microdosimetry and Cellular Morphologymentioning
confidence: 99%
“…The osteomimetic hydroxyapatite and the cellular response to a-particles Hydroxyapatite is a calcium phosphate similar to the human bone in morphology and composition insofar as it has a hexagonal structure and a similar stoichiometric calcium-to-phosphate ratio (37). Hydroxyapatite has previously been shown to induce osteogenic differentiation from cellular precursors (38) and alter the transcriptome and proteome of cocultured cells (39). Because 223 Ra exerts its effect by incorporation into the bone, we sought to assess the impact of hydroxyapatite on cellular sensitivity to a-particles using a coincubation method (Fig.…”
Section: A-particle Microdosimetry and Cellular Morphologymentioning
confidence: 99%
“…MSC differentiation has been a focus of past comparative transcriptome approaches, which has included studies of functional differences in MSC populations (Jansen et al, 2010), characterization of MSC stemness (Gao et al, 2013;Steinert et al, 2015), and assessments of differentiation status (Brown et al, 2015;Granchi et al, 2010;Liu et al, 2014;Menssen et al, 2011;Modder et al, 2012;Satija et al, 2013;Skreti et al, 2014;Steinert et al, 2015;Wislet-Gendebien et al, 2012;Yu et al, 2013;Zhang et al, 2014). For example, temporal and spatial patterns of gene expression profiles were reported for chondrogenic differentiation (Skreti et al, 2014).…”
Section: Tracking Cell Differentiationmentioning
confidence: 99%
“…According to the inverse relationship, HA has the potential to suppress adipogenesis. Several previous studies have shown that HA coating or HA discs can inhibit the adipogenesis of different cell types . For instance, Zhang et al found that HA discs composed of natural HA powder inhibited adipogenic differentiation of mouse bone marrow derived MSCs by regulating several microRNAs in the adipogenesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that HA coating or HA discs can inhibit the adipogenesis of different cell types . For instance, Zhang et al found that HA discs composed of natural HA powder inhibited adipogenic differentiation of mouse bone marrow derived MSCs by regulating several microRNAs in the adipogenesis pathway. Iijima et al have reported that HA coating and synthetic HA discs suppressed the adipogenic differentiation of hMSCs through decreasing the formation of lipid droplets and the expression of PPARγ and C/EBPα.…”
Section: Discussionmentioning
confidence: 99%